Revitalisasi Studi Hisab di Indonesia - Susiknan Azhari (Al-Jami'ah Research Centre, 2000)
This article tries to look at the study of Science of Islamic Calendar (Ḥisab) in Indonesia. In the first part of this writing, the writer shows the golden age of this science when such great Islamic scientists as al-Khawārizmi, al-Battany, al-Birūni and Ulugh Beg, flourished. The writer argues that this development was achieved because there was no dichotomy between this Science of Islamic Calendar and Astronomy. However, currently, study of Science of Islamic Calendar in the Muslim world, particularly in Indonesia, has stagnated. By examining bibliography on this study, the writer surveys the causes of this stagnancy. According to him, this condition is caused by frame of thought of dichotomy between religious knowledge and science, which in tum leads to the dichotomy between the Science of Islamic Calendar and Astronomy. The former is identified as one of religious matters and the latter is regarded as a